CLIPPERS SYNDROME - MRI FEATURES AND DIAGNOSTIC IMAGING FOLLOW-UP IN A PATIENT - CASE DISCUSSION AND REVIEW OF THE LITERATURE - Radoslav Georgiev (Peytchinski Publishing, 2023)
Chronic Lymphocytic Inflammation with Pontine Perivascular Enhancement Responsive to Steroids (CLIPPERS) syndrome is a rare neurological disorder with uncertain etiology, pathogenesis and clinical course. Pittock et al. in 2010 first described this chronic inflammatory neurologic condition, which preferably affects the brainstem. There is an infiltration with inflammatory cells of the affected regions and typical dotted and curvilinear contrast-enhancement zones on magnetic resonance imaging (MRI), including leptomeninges. I present one case of a 41-year-old male with gradual onset of suspected infectious disease and neurological worsening with typical MRI features, with a biopsy confirmed diagnosis and follow-up for 15 months. The MRI findings and the evolution of the disease can narrow the differential-diagnostic spectrum in such a clinical case.